Print Me an Organ? Ethical and Regulatory Issues Emerging from 3D Bioprinting in Medicine - Gilbert, Frederic; O’Connell, Cathal D.; Mladenovska, Tajanka; Dodds, Susan (Science and engineering ethics, 2018)
Recent developments of three-dimensional printing of biomaterials (3D bioprinting) in medicine have been portrayed as demonstrating the potential to transform some medical treatments, including providing new responses to organ damage or organ failure. However, beyond the hype and before 3D bioprinted organs are ready to be transplanted into humans, several important ethical concerns and regulatory questions need to be addressed. This article starts by raising general ethical concerns associated with the use of bioprinting in medicine, then it focuses on more particular ethical issues related to experimental testing on humans, and the lack of current international regulatory directives to guide these experiments. Accordingly, this article (1) considers whether there is a limit as to what should be bioprinted in medicine; (2) examines key risks of significant harm associated with testing 3D bioprinting for humans; (3) investigates the clinical trial paradigm used to test 3D bioprinting; (4) analyses ethical questions of irreversibility, loss of treatment opportunity and replicability; (5) explores the current lack of a specific framework for the regulation and testing of 3D bioprinting treatments.